Sams Teach Yourself HTML and CSS in 24 Hours, Seventh Edition - Oliver, Dick; Morrison, Michael (Sams, 2005)
Learn from the newest, updated edition of the highly acclaimed introduction to HTML, Sams Teach Yourself HTML and CSS In 24 Hours . The seventh edition includes updates to introduce Cascading Style Sheets (CSS) in concert with HTML to produce quality web pages. You'll be able to study revisions that refine examples, as well as provide an enhanced integration with your web pages. You'll also gain a comprehensive understanding with new examples that match the current state of HTML. This carefully organized, well-written tutorial teaches beginning web page development skills, covering only those HTML and CSS tags that are likely to be used on creating a beginning web page. The 24 separate, one hour-long tutorials follow the process by which you should be creating your web page, building knowledge not only of how to create a web page, but building a general knowledge of how to use HTML and CSS in other projects as well. Chapters include: Understanding HTML and XHTML Creating Your Own Web Page Graphics Using Tables to Organize and Lay Out Your Pages Using Style Sheets for Page Layout Dynamic Web Pages.